When less is less: the complexities of growth and the degrowth company - TALBOT, LORRAINE (Journal of law and society, 2024)
In this article, I take issue with settled claims that the organizational features of the corporation make it the most effective enabler of growth under capitalism – an assumption that has focused various growth‐critical narratives on mechanisms to regulate corporate growth. I argue that such narratives are flawed because, far from always blindly amplifying growth, the corporate form often operationalizes degrowth to protect capital. This argument is theoretically grounded in Marx's analysis of the particularities of growth under capitalism, and a law‐in‐context analysis of how companies operationalize degrowth to protect capital/shareholder interests, utilizing the examples of takeovers and share repurchases. The article shows that narratives seeking to both protect the environment and deliver human flourishing need to be contextualized within an understanding of the specifics of growth under capitalism and the function of corporate law architecture.